Observation Of The Growth And Development Of Stunted Toddlers - Lisni, Lisni; Fitriani, Aida; Wahyuni, Yenni Fitri; Mawarni, Serlis; Us, Hafsah; Friscila, Ika (JKM (Jurnal Kebidanan Malahayati), 2024)
Latar Belakang: Anak dengan keadaan stunting memiliki aktivitas motorik yang rendah, perkembangan motorik dan mental yang terlambat dan kemampuan kognitif yang terhambat. Keterlambatan tumbuh kembang anak sangat membahayakan jika terjadi pada periode emas atau golden periode, dimana pada masa tersebut anak sedang mengalami pertumbuhan pesat yang menjadi bekal ketika remaja dan dewasa.Tujuan: memberikan hasil observasi tumbuh kembang balita stunting di wilayah kerja Puskesmas Bebesen Kabupaten Aceh Tengah.Metode:  penelitian kuantitatif deskriptif dengan desain cross sectional. Sampel sebanyak 33 anak menggunakan Teknik purposive sampling.Hasil: Hasil penelitian yang dilakukan pada 33 anak di wilayah kerja Puskesmas Bebesen, dari aspek rasio berat badan/usia, dominan anak dalam kondisi normal. Dari aspek tinggi badan/usia, dominan dalam kondisi "Sangat Pendek" dan "Pendek". Dari aspek berat badan/tinggi badan dominan dalam kondisi "Gizi Baik". Hasil observasi DDST II pada keseluruhan sampel, baik dari sisi personal sosial, motorik kasar, bahasa, dan motorik halus, semua dominan mengalami keterlambatan. Kesimpulan: Bahwa anak dengan stunting mengalami keterlambatan tumbuh kembang baik dari sisi personal sosial, motorik kasar, bahasa, dan motorik halus.Saran: Pencegahan kejadian stunting lebih tepat dilakukan untuk menghindari keterlambatan tumbuh kembang pada anak yang dapat membahayakan. Kata Kunci : Stunting, Tumbuh Kembang, Observasi, Balita ABSTRACT Background: Children with stunting have low motor activity, delayed motor and mental development and inhibited cognitive abilities. Delayed growth and development of children is very dangerous if it occurs during the golden period, where at that time the child is experiencing rapid growth which becomes provisions for adolescence and adulthood.Purpose:  To provide the results of observations of the growth and development of stunted toddlers in the work area of the Bebesen Health Center, Central Aceh Regency.Methods:  Descriptive quantitative research with a cross-sectional design. A sample of 33 children using the purposive sampling technique.Results: The results of the study conducted on 33 children in the work area of the Bebesen Health Center, from the aspect of the weight/age ratio, the dominant children are in normal condition. From the aspect of height/age, the dominant ones are in the "Very Short" and "Short" conditions. From the aspect of weight/height, the dominant ones are in the "Good Nutrition" condition. The results of the DDST II observations on the entire sample, both in terms of personal social, gross motor, language, and fine motor, all are predominantly delayed.Conclusion: Children with stunting experience delayed growth and development in terms of personal social, gross motor skills, language, and fine motor skills.Suggestions; Prevention of stunting is more appropriate to avoid delayed growth and development in children that can be dangerous. Keywords: : Stunting, Growth and Development, Observation, Toddler